CHANGE MONITORING OF THE DNIPRО RIVER WITHIN KYIV USING SATELLITE INFORMATION - Tomchenko, Olha; Panchenko, Roman; Mazurkevich, Lyudmila (Water and Water Purification Technologies. Scientific and Technical News, 2020)
The dynamics of overgrowth of aquatic vegetation of the Dnipro River within the city of Kyiv in the period from 2005 to 2017 was studied using satellite information and ground data and a causal relationship between climate change and overgrowing processes was established. Based on the results of systematization and the analysis of the land hydrological data obtained in the archives of the CGO SESU of Ukraine, the graphs showing the dynamics of changes in average annual air temperature and water temperature, water level, its expenses within Kyiv were constructed. Investigating the influence of climatic factors, it was found that the temperature of the summer months has risen by about 2ºC over the last decade. It is assumed that the change of this factor leads to the change and destruction of the hydrological regime of the river. First of all, the flow velocity, the average annual water temperature, the total runoff volume, the evaporation volume from the Dnipro River surface and others change. This changes, together with the influence of major anthropogenic factors leads to the progress of overgrowth and «algal blooms» of the river. It is established that during the period from 2010 to 2017, the area of overgrown Dnipro River within Kyiv increased more than 2 times, and was already 2.1 km2, which is 7.5% of the total water surface. It was found that the largest areas of overgrowth are in small bays and straits of the Dnipro River, for the period from 2005 to 2017 the percentage of overgrowth of the water surface in the bays increased and amounted to 14.5 %, which is almost 5 times more than in 2005.